Role of service quality and customer satisfaction in firm's performance: Evidence from Pakistan hotel industry - Syed Naseeb Ullah Shah; Shahid Jan; Qadar Bakhsh Baloch (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The purpose of the study is to investigate the effect of customer's satisfaction and service quality towards the hotels' performance by applying SERVQUAL model. The data was collected from the 1429 hotel customers of selected cities of Khyber Pakhtunkhwa (Peshawar, Swat, Chitral, Naran, Abbottabad, Galiat), Punjab (Lahore, Rawalpindi) and the capital city (Islamabad) of Pakistan. The sample of hotels comprised of 10 hotels from each city and 20 customers at each hotel were taken as respondents. The researchers used regression and factor analysis for analyzing the data. The results revealed that service attributes have a significant optimistic effect on customer satisfaction. Moreover, service assurance is found significantly negative predictor of customer satisfaction. Consequences of the study exhibit that constructive connection exists amid expected and actual attributes of service quality and customer satisfaction. The study considered that the hotel customers experience is the key factor in the hospitality industry.
Keywords: 330; customer satisfaction; service quality; competitive advantage; SERVQUAL; hospitality industry